Electrochemical study of hydrogen absorption in polycrystalline palladium - Salvarezza, Roberto Carlos (1991)
The hydrogen reactions on polycrystalline Pd in 0.1 M NaOH at 25°C have been studied by using transients at constant potential, and by impedance spectroscopy and X-ray diffraction techniques. At potentials, Es, more positive than the reversible potential, Er, for the H2 evolution reaction, the current-time response and the impedance data indicate H atom diffusion into the bulk Pd. The X-ray diffraction pattern of electrodes cathodized during 20 min at these potentials are similar to those obtained for Pd. At Es < Er, the current transients exhibit a current maximum which increases as Es moves in the negative direction. The Nyquist plot for the rising part of the transients indicates the H atom diffusion into the bulk metal and H2 evolution on the Pd surface at high frequencies. The X-ray diffraction pattern of the electrodes cathodized at Es < Er, shows the presence of the βPdH phase and Pd. The experimental results indicate that different reactions take place simultaneously in this potential range: (i) Hs evolution, (ii) H diffusion into the bulk Pd, (iii) nucleation and diffusion-controlled growth of the βPdH phase. Taking into account the contribution of these reactions, a model, which is able to reproduce the experimental current transients, is presented.